Quality assessment of clinical practice guidelines on the treatment of hepatocellular carcinoma or metastatic liver cancer. - Yingqiang Wang (Public Library of Science (PLoS), 2014)
Objectives To assess the quality of the currently available clinical practice guidelines (CPGs) for hepatocellular carcinoma, and provide a reference for clinicians in selecting the best available clinical protocols. Methods The databases of PubMed, MEDLINE, Web of Science, Chinese Biomedical Literature database (CBM), China National Knowledge Infrastructure (CNKI), WanFang, and relevant CPGs websites were systematically searched through March 2014. CPGs quality was appraised using the Appraisal of Guidelines for Research & Evaluation (AGREE) II instrument, and data analysis was performed using SPSS 13.0 software. Results A total of 20 evidence-based and 20 expert consensus-based guidelines were included. The mean percentage of the domain scores were: scope and purpose 83% (95% confidence interval (CI), 81% to 86%), clarity of presentation 79% (95% CI, 73% to 86%), stakeholder involvement 39% (95% CI, 30% to 49%), editorial independence 58% (95% CI, 52% to 64%), rigor of development 39% (95% CI, 31% to 46%), and applicability 16% (95% CI, 10% to 23%). Evidence-based guidelines were superior to those established by consensus for the domains of rigor of development (p<0.001), clarity of presentation (p = 0.01) and applicability (p = 0.021). Conclusions The overall methodological quality of CPGs for hepatocellular carcinoma and metastatic liver cancer is moderate, with poor applicability and potential conflict of interest issues. The evidence-based guidelines has become mainstream for high quality CPGs development; however, there is still need to further increase the transparency and quality of evidence rating, as well as the recommendation process, and to address potential conflict of interest.